Ladies of Toronto (ed Elizabeth Driver): The Home Cook Book - Davidson, Alan (Petits Propos Culinaires, 2024)
Ladies of Toronto (ed Elizabeth Driver): The Home Cook Book (facsimile reprint of 1877 edn):  Whitecap Books, 351 Lynn Ave., N. Vancouver, British Columbia, Canada V7J 2C4, 2002: ISBN 1552853489: 384 pp, h/b, US$14.95.